497 Longitudinal immune profiling reveals unique myeloid and T cell phenotypes associated with spontaneous immunoediting in a novel prostate tumor model. (9th November 2020) - Ager, Casey; Obradovic, Aleksander; Arriaga, Juan; Chaimowitz, Matthew; Abate-Shen, Cory; Califano, Andrea; Drake, Charles
Abstract : Background: The theory of cancer immunoediting, which describes the dynamic interactions between tumors and host immune cells that shape the character of each compartment, is foundational for understanding cancer immunotherapy. Few models exist that facilitate in-depth study of each of the three canonical phases of immunoediting: elimination, equilibrium, and escape. Here, we perform high dimensional longitudinal immune profiling of NPK-C1, a transplantable prostate tumor model that recapitulates the three phases of immunoediting spontaneously in immunocompetent C57BL/6 animals. Methods: We generated a 28-color immune phenotyping panel to interrogate the NPK-C1 microenvironment using a Cytek Aurora spectral flow cytometer. We analyzed NPK-C1 tumors on days 10, 15, 20 and 24 post-implantation, representing elimination, equilibrium, early escape, and late escape phases, respectively. These data were analyzed by both traditional gating and with an optimized dimensionality reduction and unsupervised clustering workflow. We additionally performed in vivo depletion studies of T cell and granulocyte subsets at early and late time points to determine if these bulk populations are required for immunoediting during elimination and equilibrium/escape. Results: We found that a cluster of activated CD4 effector T cells were enriched early during elimination phase and were overrepresented in NPK-C1 tumors which regress rather than progress to escape. CD4 in vivo depletion studies validated a functional role for CD4 T cells in suppressing NPK-C1 progression at these phases. Additionally, a central memory-like cytotoxic CD8 T cell cluster was enriched in regressing NPK-C1 tumors, and CD8 depletion allowed NPK-C1 progression throughout immunoediting. Regulatory T cells (Tregs) as a whole were counterintuitively enriched in regressing tumors, however high dimensional analysis revealed their significant phenotypic diversity, with a number of Treg subpopulations enriched in progressing tumors. In the myeloid compartment, we found that iNOS+ DC-like cells were enriched in regressing tumors, while CD103+ DCs were counterintuitively associated with late stage tumor progression. Conclusions: These data introduce a new model – NPK-C1 – to study immunoediting and suggest both CD8 and CD4 T cells are required to suppress tumor outgrowth throughout each phase of cancer immunoediting, while myeloid populations exhibit significant phenotypic and functional diversity throughout this process. Further, our identification of unique sub-populations of myeloid and T cells correlating with either regression or progression to escape highlights a role for multi-dimensional flow-based analyses to more deeply understand immune cell dynamics in the tumor microenvironment. Ethics Approval: All experiments and procedures for this study were approved by the Columbia University Medical Center Institutional Animal Care and Use Committee (IACUC)